Study of the Electrophoretic Behavior of Cephalosporins by Capillary Zone Electrophoresis - Gabriel Hancu; Adina Sasebeşi; Aura Rusu; Hajnal Kelemen; Adriana Ciurba (Tabriz University of Medical Sciences, 2015)
Purpose: The aim of the study was the characterization of the electrophoretic behavior of cephalosporins from different generation having different structural characteristics in order to develop a rapid, simple and efficient capillary electrophoretic method for their identification and simultaneous separation from complex mixtures. Methods: Ten cephalosporin derivatives (cefaclor, cefadroxil, cefalexin, cefazolin, cefoxitin, cefuroxime, cefoperazone, cefotaxime, ceftazidime, ceftriaxone) were analyzed by capillary zone electrophoresis using different background electrolyte solutions at different pH values. Electrophoretic mobilities of the analytes were calculated, the influence of the electrophoretic parameteres on the separation was established and the analytical conditions were optimized. Results: Taking into consideration their structural and chemical properties cephalosporins can be detected over a pH range between 6 and 10. The best results were obtained using a buffer solution containing 25 mM disodium hydrogenophosphate - 25 mM sodium dihydrogenophosphate, at a pH - 7.00, + 25 kV voltage at a temperature of 25 C, UV detection at 210 nm. Using the optimized analytical conditions we achieved the simultaneous baseline separation for seven cephalosporins in less then 10 minutes. Conclusion: Using the described optimized electrophoretic procedures, capillary electrophoresis can be used for the identification and determination of cephalosporins in formulated pharmaceutical products and for their separation from complex mixtures.